Petrology New Perspectives and Applications - Ismail Al-Juboury, Ali (IntechOpen, 2012)
Petrology, New Perspectives and Applications is designed for advanced graduate courses and professionals in petrology. The book includes eight chapters that are focused on the recent advances and application of modern petrologic and geochemical methods for the understanding of igneous, metamorphic and even sedimentary rocks. Research studies contained in this volume provide an overview of application of modern petrologic techniques to rocks of diverse origins. They reflect a wide variety of settings (from South America to the Far East, and from Africa to Central Asia) as well as ages ranging from late Precambrian to late Cenozoic, with several on Mesozoic/Cenozoic volcanism.